Medieval childhood : archaeological approaches - Hadley, D. M. (Dawn M.), 1967-; Hemer, K. A. (Katie A.) (Childhood in the past monograph series, 2014)
The nine papers presented here set out to broaden the recent focus of archaeological evidence for medieval children and childhood and to offer new ways of exploring their lives and experiences. The everyday use of space and changes in the layout of buildings are examined, in order to reveal how these impacted upon the daily practices and tasks of household tasks relating to the upbringing of children. Aspects of work and play are explored: how, archaeologically, we can determine whether, and in what context, children played board and dice games? How we may gain insights into the medieval count.